The economics of colonialism in Korea rethinking Japanese rule and aftermath - Kimura, Mitsuhiko 1951-
"From 1910 to 1945, Korea was a colony of Imperial Japan. Its governance has been described politically in terms of harsh oppression and economically as exploitation and impoverishment. Certainly, there were many problems with Japanese rule in Korea, but how accurate are those claims? What is the connection between the post-war development of South Korea and the socialist regime in North Korea? This book focuses on economic issues, sticks to positivism, and depicts the reality and transformation of Korea during the period of Japanese control"